Challenges of the Anti-Trump Movement - Tarrow, Sidney; Meyer, David S. (PARTECIPAZIONE E CONFLITTO, 2019)
This article explains the sudden and strong emergence of a movement in resistance to the presidency of Donald Trump as a countermovement to the long-term "movementization" of the Republican Party in the wake of civil rights, the Nixon "southern strategy", and the emergence of white nativism. It identifies the Resistance as posing three distinct challenges for both citizens and scholars of participation and conflict: the political opportunity challenge, the coalitional challenge, and the radicalization/institutionalization challenge. The article situates the Resistance in a historical and comparative context, highlights its dilemmas as it faces the focal point of a populist/nativist President, and asks if it is an effective countermovement to the white nativist movement that supports him.